Educating the Public on the Health Risks of Very Low Nicotine Content Cigarettes: Results From a US-Based Convenience Sample. Issue 6 (12th January 2022) - Differding, MacKenzie; Katz, Sherri Jean; Strayer, Lori G; White, Cassidy; Strasser, Andrew A; Donny, Eric C; Hatsukami, Dorothy K; Carroll, Dana Mowls
Abstract: Introduction: US FDA issued an advance notice of proposed rulemaking to reduce nicotine in cigarettes. To maximize the benefits of this potential standard, very low nicotine content (VLNC) cigarettes must be communicated in a way that does not result in misperceptions. Aims and Methods: Adults ( n = 567 who smoke; n = 610 non-smokers) from an online platform were randomized to a control message previously associated with accurate addictiveness perceptions of VLNC cigarettes but health misperceptions or to one of five messages that also included messaging on nicotine morbidity effects or VLNC cigarettes morbidity or mortality effects. p value <.01 was significant. Results: In participants who smoke, perceived lung cancer risk (responses: 1, very little risk to 10, very high risk ) if smoked VLNC cigarettes regularly was higher in conditions that communicated mortality effects of VLNC cigarettes compared to the control (7.12–7.18 vs. 5.97, p values < .01). In non-smokers, perceived lung cancer risk was higher in all five message conditions when compared with the control (7.58–8.22 vs. 6.35, p values < .01). Proportion who responded accurately (ie, False ) to the statement Cigarettes with 95% less nicotine are safer than cigarettes with normal nicotine levels was higher in conditions describing VLNC morbidity or mortality effects when compared with the control in both participants who smoke (52.04–67.37% vs. 30.85%, p values < .01) and do not smoke (62.50–72.38% vs. 32.00%, p values < .01). Conclusions: Messaging on mortality effects of VLNC cigarettes (ie, cigarettes with 95% less nicotine are as deadly as current cigarettes ) was associated with more accurate perceptions of the health risks of VLNC cigarettes than the control; however, misperceptions remained in one-third of participants. Implications: One approach to communicating a VLNC cigarette standard to the public is to include messaging on the mortality effects of VLNC cigarettes. However, further study and possible refinement of this message condition are recommended since approximately one-third of participants exposed to this message still perceived VLNC cigarettes to be safer than normal nicotine content cigarettes.